Integrating whole genome and transcriptome sequencing to characterize the genetic architecture of isoform variation - Liu, Chunyu; Joehanes, Roby; Ma, Jiantao; Xie, Jiuyong; Yang, Jian; Wang, Mengyao; Huan, Tianxiao; Hwang, Shih-Jen; Wen, Jia; Sun, Quan; Demirkale, Cumhur Y.; Heard-Costa, Nancy L.; et al. (Nature communications, 2025)
We present a whole-blood isoform ratio QTL (irQTL) resource by analyzing genome-wide isoform-to-gene expression ratios using sequencing data. In Framingham Heart Study (FHS, n = 2622) discovery, we identify over 1.1 million cis -irQTLs (minor allele frequency [MAF] ≥ 0.01, ±1 Mb of 10,883 isoform transcripts, P < 5 × 10 −8 ) across 4,971 genes. Among 11,425 sentinel cis -irQTLs, 72% replicate ( P < 1 × 10 −4 ) in the Women’s Health Initiative (WHI; n = 2005). Notably, 20% of cis -irQTLs have no significant association with overall gene expression, indicating isoform-specific regulation. These variants are enriched at splice donor/acceptor sites and genome-wide association study loci ( P < 1 × 10 −10 ). We also identify 1870 sentinel trans -irQTLs (MAF ≥ 0.01, P < 1.5 × 10 −13 ) for 1,084 isoforms across 590 genes, and 2327 rare cis -irQTLs (0.003 < MAF < 0.01) for 2467 isoforms of 1428 genes in FHS, with external replication rates of 61% and 41% in WHI, respectively. We highlight rs12898397 in ULK3 , which alters splice site usage and reduces expression of a full-length isoform. Mendelian randomization supports a causal role between this isoform shift and reduced diastolic blood pressure. These findings highlight the power of irQTL mapping to uncover transcript-specific regulatory mechanisms underlying complex traits. Here the authors use a genome-wide approach to identify genetic variants associated with RNA isoform variation, uncovering new links between transcriptional regulation and complex traits. The findings can advance understanding of disease mechanisms.